Determining Student Achievements using Multicriteria Approach with Electre Method - Achmad Jauhari; Yudha Dwi Putra Negara; Faisol Arif Efendi; Fifin Ayu Mufarroha; Devie Rosa Anamisa; Abdullah Basuki (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
. In the field of education, assessing student achievement is critical for determining students' levels of success and academic progress. However, the high cost of desire is frequently complicated since it incorporates a variety of student characteristics and aspects that must be taken into account. In this study, a multi-criteria approach using the ELECTRE method was suggested to measure student achievement holistically. The ELECTRE technique is a multi-criteria analysis method that employs a comparison matrix to evaluate alternatives based on a variety of criteria. This way to evaluate student progress allows for more accurate and objective decision-making than a single strategy that focuses on a single factor. An application was created to make its use easier. Applications that can be utilized to assist determine excellent students via black box testing are stated to be successful because 33 features provided in the application work as intended. This study is expected to help improve student accomplishment assessment policies and methods at various levels of education.